Penafsiran KH. M. Zen Syukry dalam Kitab Qutul Qalbi QS. Al-Ikhlas 1-4: Sebuah Kajian Hermeneutika Fungsi Interpretasi Jorge J.E Gracia - Fitra Rizkikah; Subhi Nur Isnaini (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
This article discusses how the interpretation of KH. M. Zen Syukry in the book Qutul Qalbi QS. Al-Ikhlas 1-4 are analyzed using the theory of Function Interpretation of Jorge JE Gracia. The research methodology used in this research is qualitative with the type of library research (Library Research) through a descriptive analysis approach (descriptive analytic). From the analysis of the interpretation function theory of Jorge JE Gracia. KH. M. Zen Syukry has fulfilled the elements of the theory of the function of gracia interpretation of his interpretation; On the historical function KH. M. Zen Syukry explained about the fall of (asbabun–nuzul) Qs. Al-Ikhlas, namely when the Prophet Muhammad was asked by the polytheists about your God, then QS. Al-Ikhlas. In the function of developing meaning (meaning function) KH. M. Zen Syukry explains that Allah is a Essence that is exist (which must exist), and explains the meaning of the verses contained in it. Implication function (implicative function); its application is to use reason and Allah's guidance so that monotheism enters the soul, he continued, when mentioning Allah, one must recite with the heart. Because this interpretation is very thick with nuances of Sufi interpretation. So for further research it is recommended to use other hermeneutic theories in order to find reading results from other reading points of view.